The Self-Naming System of the Bugis Community: A Lexical Semantic and Ethnolinguistic Study - AMIR, Johar; NENSILIANTI (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Every individual receives a proper name (anthroponym) from their parents as their first property. Naming then becomes the starting point for an individual’s introduction to his new environment. Besides that, an individual cannot declare his true self as existing, but through a self-name, he is known. It plays a vital role as one of the communication network devices between the self and its environment. Additionally, proper names serve as conventional signs of social identification. We designed this study using a qualitative approach to describe the Bugis community’s proper name system. The data for this research are samples of Bugis people’s proper names and supporting information obtained from informants. This research relies on written and oral data sources. The data collection techniques employed in this research include library research, in-depth interviews, and focus group discussions (FGDs). This analysis process encompasses both in-field and post-data collection analyses. During the field analysis, we narrowed the study based on the established focus, asked analytical questions to trace the data, made schematic memos of the research, and continuously conducted literature reviews. Once collected, we used qualitative analysis to describe the Bugis community’s self-naming system and its shifting patterns. The Bugis system of proper names includes one-word constructions, two-word constructions, three-word constructions, and four-word constructions. We can divide Bugis proper names into two categories based on their construction: basic form (monomorphemic) and complex form (polymorphic); based on the number of syllables, we can divide them into two-syllable, three-syllable, and four-syllable proper names; based on the formation process, we can separate them into proper names that undergo processes such as word omission or shortening, sound change or exchange, sound addition, and sound adjustment; in terms of the categories of words that form them, Bugis proper names in the form of one word, both basic form (monomorphemic) and complex form (polymorphic), are generally noun, verb, and adjective word classes.